ANALISIS PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG ATAS OBJEK HAK TANGGUNGAN DALAM PUTUSAN Nomor 425/Pdt.G/PN Bdg - NIM. A1012211170, NABILA (Jurnal Fatwa Hukum, 2025)
Abstract This study analyzes legal protection for auction winners of mortgaged property under Law Number 4 of 1996 concerning Mortgage Rights and other related regulations. Execution auctions for mortgaged property are an important mechanism for resolving problem loans, but in practice, they often give rise to administrative issues, resulting in obstacles for auction winners in controlling and registering ownership of the property they have won. The main issue relates to achieving legal certainty for auction winners who have complied with all applicable legal procedures. This study uses a normative juridical method with a statutory approach, a conceptual approach, and a specific case analysis. The objective of the study is to examine the applicable forms of legal protection and legal certainty in Decision Number 425/PDT.G/2020/PN.BDG and to identify obstacles to the realization of legal protection for auction winners. The results indicate that legal protection encompasses a preventive dimension through the regulatory framework and a repressive dimension through the civil lawsuit mechanism. The panel of judges recognized the auction winners as buyers in good faith entitled to full protection based on the principles of legal certainty and good faith. However, material legal certainty remains hampered by weak administrative coordination between the KPKNL (National Land Agency) and the National Land Agency (BPN). Improvements to the administrative system and land data integration are needed to ensure substantive legal protection for auction winners. Keywords: Legal Protection, Execution Auction, Mortgage Rights, Auction Winner, Legal Certainty. . Abstrak This study analyzes legal protection for auction winners of mortgaged property under Law Number 4 of 1996 concerning Mortgage Rights and other related regulations. Execution auctions for mortgaged property are an important mechanism for resolving problem loans, but in practice, they often give rise to administrative issues, resulting in obstacles for auction winners in controlling and registering ownership of the property they have won. The main issue relates to achieving legal certainty for auction winners who have complied with all applicable legal procedures. This study uses a normative juridical method with a statutory approach, a conceptual approach, and a specific case analysis. The objective of the study is to examine the applicable forms of legal protection and legal certainty in Decision Number 425/PDT.G/2020/PN.BDG and to identify obstacles to the realization of legal protection for auction winners. The results indicate that legal protection encompasses a preventive dimension through the regulatory framework and a repressive dimension through the civil lawsuit mechanism. The panel of judges recognized the auction winners as buyers in good faith entitled to full protection based on the principles of legal certainty and good faith. However, material legal certainty remains hampered by weak administrative coordination between the KPKNL (National Land Agency) and the National Land Agency (BPN). Improvements to the administrative system and land data integration are needed to ensure substantive legal protection for auction winners. Keywords: Legal Protection, Execution Auction, Mortgage Rights, Auction Winner, Legal Certainty.